Chromoblastomycosis complicated with co-morbidities, curbed by cryotherapy: a case report - Ittigi, Vivekananda; Hegde, Soumya G. (International Journal of Research in Dermatology, 2019)
Chromoblastomycosis is a chronic mycosis affecting skin and subcutaneous tissue. Treatment of chromoblastomycosis is challenging due to refractory nature of the condition and varied antifungal sensitivity of the organism. Though systemic antifungals are commonly used modality of treatment, there is no “gold standard” treatment. The array of treatment options include chemotherapy and physical methods (cryosurgery/ CO2 laser/superficial X-rays/ surgical excision), either alone or in combination. A 60 year old male farmer presented with history of congestive cardiac failure (CCF), presented with gradually increasing painful, reddish elevated skin lesions over right knee since 2 years. On examination, there was a well-defined solitary, tender plaque of size 2×3 cm with smooth surface, elevated peripheral margin. Blood investigations were within normal limits except for deranged LFT. Diagnosis of chromoblastomycosis was made based on KOH mount which revealed typical sclerotic bodies and histopathology which revealed neutrophilic abscesses, muriform cells, mixed granulomatous response. In view of his comorbidities like congestive cardiac failure and deranged liver function test, we couldn’t consider the possibility of systemic drugs like Itraconazole. So, he was treated only with liquid nitrogen cryotherapy on a weekly basis for 8 weeks. Marked improvement in lesion was observed after 8 sittings. In our case, due to cardiac complications and deranged liver function test we treated the patient with cryotherapy solely and achieved marked improvement in skin lesions. Cryotherapy alone serves as an effective treatment modality when systemic antifungals can’t be given.